Object Lives and Global Histories in Northern North America Material Culture in Motion, C. 1780 - 1980. - Lemire, Beverly (McGill-Queen's/Beaverbrook Canadian Foundation Studies in Art History Ser., 2021)
An original perspective on the history of northern North American peoples grounded in things, this book explores how close, collaborative looking can discern the traces of contact, exchange, and movement of objects and give them a life and political power in complex cross-cultural histories.